ALL THE WORDS THAT ARE NOT FIT TO PRINT. NOTES ON THE “ILLITERATURE” OF ITALIAN EMIGRATION (Italiano LinguaDue, 2012)
L’articolo presenta criticamente alcuni esempi dell’uso dell’italiano in emigrati negli Stati Uniti di prima e seconda generazione: esempi a metà strada fra scritto e orale, rinvenibili in scritte murarie e corrispondenze private (cartoline illustrate e lettere); messaggi personali si alternano a prove poetiche amatoriali, in uno stretto dialogo con le immagini. Nel complesso, il contributo fornisce indicazioni intorno al lento passaggio da una lingua all'altra, testimoniato da peculiari adattamenti a livello fonetico, lessicale, sintattico.This article presents a few examples of the use of Italian in first and second-generation immigrants to the United States: examples half-way between written and oral language are taken from writing on walls, post cards, memoirs and poetry, in intimate dialogue with images. On the whole, the paper considers the slow shift from one language to another, as shown by particular adaptations on phonetic, lexical and syntactic levels.